EFEKTIVITAS SATUA I BELOG SEBAGAI MEDIA PEMBELAJARAN LITERASI DI SEKOLAH DASAR - Ida Bagus Yoga Swadnyana; I Wayan Sujana; Ida Bagus Manuangga Pradnyana; I Nyoman Surya Yudistira; I Made Bhayu Dwipayana Setiawan; I Komang Adanda Wira Suputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted based on the low reading interest of elementary school students and the limited variety of literacy learning media used in the learning process. The study aimed to determine the effectiveness of Satua I Belog as a literacy learning medium in improving the reading interest of fifth-grade students at SD Negeri 3 Duda Timur. This research employed a quantitative approach with a pre-experimental method using the One Group Pretest-Posttest Design. The research subjects consisted of 28 students, including 15 male students and 13 female students. Data were collected through questionnaires, observations, and documentation. The collected data were analyzed using descriptive statistics and inferential statistics through the paired sample t-test. The results showed that the use of Satua I Belog was effective in increasing students’ reading interest. This was indicated by the increase in the average reading interest score from 62.32 in the pretest to 84.71 in the posttest.The hypothesis testing results revealed that the calculated t-value of 8.521 was higher than the t-table value of 2.052, with a significance value of 0.000 < 0.05. Therefore, H0 was rejected and H1 was accepted. In addition to improving reading interest, the use of Satua I Belog also increased students’ engagement in learning activities, fostered students’ interest in reading, and helped instill moral values and Balinese local culture. Therefore, Satua I Belog can be used as an effective literacy learning medium to support the development of literacy culture in elementary schools.